Bronchial reactivity to inhaled histamine and annual rate of decline in FEV1 in male smokers and ex-smokers. Issue 1 (January 1985) - Taylor, R G; Joyce, H; Gross, E; Holland, F; Pride, N B
Abstract : We examined the relations between bronchial reactivity, baseline FEV1, and annual decline of height corrected FEV1 (delta FEV1/ht3) over 7.5 years in 227 men (117 smokers, 71 ex-smokers, and 39 non-smokers). Men with a clinical diagnosis of asthma or receiving bronchodilator treatment were excluded. Bronchial reactivity was determined as the provocation concentration (PC20) of inhaled histamine sufficient to reduce FEV1 by 20%; subjects were divided into reactors (PC20 less than or equal to 16 mg/ml) and non-reactors (PC20 greater than 16 mg/ml). Thirty per cent of smokers, 24% of ex-smokers, and 5% of non-smokers were reactors. When smokers who were reactors were compared with non-reactors, the reactors showed a lower baseline FEV1 as percentage predicted in 1981-2 (85% v 108%), and a faster delta FEV1/ht3 (14.1 v 9.2 ml/y/m3). Baseline FEV1 correlated with PC20 in both smokers (rs = 0.51) and ex-smokers (rs = 0.61), and all 15 subjects with an FEV1 under 80% of the predicted value were reactors. In ex-smokers delta FEV1/ht3 was similar in reactors and non-reactors (m 9.0 v 7.4 ml/y/m3), despite significant differences in baseline FEV1. When analysis was confined to men with a baseline FEV1 over 80% predicted, the prevalence of reactors was significantly increased among smokers and slightly increased among ex-smokers compared with non-smokers, though the mean FEV1 was higher in the non-smokers. Bronchial reactivity was not increased in smokers aged 35 years or less. In smokers delta FEV1/ht3 was faster in those with a personal history of allergy (usually allergic rhinitis), but was not related to a family history of allergic disease, total serum immunoglobulin E level, absolute blood eosinophil count, or skinprick test score. delta FEV1/ht3 was also faster in all subjects taking beta blocker drugs. Thus increased bronchial reactivity was associated with accelerated decline of FEV1 in smokers. Although the association could be a consequence of a lower lower baseline FEV1, a trend towards increased reactivity was found in smokers with normal baseline FEV1 and delta FEV1/ht3 was dissociated from increased reactivity in ex-smokers. These findings are compatible with the "Dutch hypothesis, " but the association between allergic features and accelerated delta FEV1/ht3 was relatively weak, and increased reactivity may follow rather than precede the onset of smoking.